Libraries in Web 2.0 environment - Banek Zorica, Mihaela (Array, 2009)
Changes in the Web environment have influenced all aspects of human professional and leisure behaviour. As libraries main purpose has always been to respond to its users’ information needs the transition currently affecting information environment has posed new challenges on them. Paper presents overview of the definitions and insights into the Library 2.0 concept looking at its both positive and negative aspects.